Design Enhancent and Comparative Analysis of Low Torque Ripple Double-Stator Switched Reluctance Motor - Das Gupta T.; Dhary K. (My University, 2025)
This paper presents the comprehensive design enhancement and comparative analysis of a low torque ripple double-stator switched reluctance motor for industrial applications. The Doublestator switched reluctance motors (DSSRMs) are gaining popularitydue to their high torque density than the conventional toothswitched reluctance motors (TSRM). The main limiting performance parameter for such motors to be adapted for industrial application is their high torque ripple.The design methodology of an improved 12/10 pole DSSRM has already been reported which has the characteristics of very low torque ripplesin a wide speed range. However, its detailed comparative analysis with other motors has not been described in the previous literature.This paper further investigates the comparative analysis of thisimproved motor with the baseline DSSRM and conventional TSRMwith the help of2D finite-element analysis. Comparison is done in the context of average torque, torque ripple, iron and copper weight requirement, harmonic analysis of torque ripple frequency, losses and efficiency.Simulation results conferthe effectiveness of the improved DSSRM overthe other two machines. © JES 2022 on-line: journal/esrgroups.org/jes